2020
DOI: 10.3928/24748307-20200217-01
|View full text |Cite
|
Sign up to set email alerts
|

Embedding a Health Literacy Intervention Within Established Parenting Groups: An Australian Feasibility Study

Abstract: Background: A significant proportion of new parents in high-income countries have lower health literacy, but few health literacy interventions exist for this group. Objective: This study investigated the feasibility of delivering health literacy content within existing postnatal parenting groups. Methods: Multicenter feasibility study using a seven-group pre-test post-test design. Parents older than age 16 years with children between age 4 and 26 weeks with sufficient English fluency were invited to participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Findings from feasibility testing ( Muscat et al, 2020 ) were incorporated into version 2 of the Parenting Plus program in collaboration with health care staff and patient partners. The codesign process identified patient and staff priorities for revision and ensured modifications adequately addressed underlying issues.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from feasibility testing ( Muscat et al, 2020 ) were incorporated into version 2 of the Parenting Plus program in collaboration with health care staff and patient partners. The codesign process identified patient and staff priorities for revision and ensured modifications adequately addressed underlying issues.…”
Section: Resultsmentioning
confidence: 99%
“…In July 2020, we reported on a study that assessed the feasibility of embedding a group-based health literacy skills training program (Parenting Plus, version 1) within established parenting groups in New South Wales (NSW), Australia ( Muscat et al, 2020 ). Findings indicated that staff and parents wanted more information about parenting topics (e.g., starting solid foods) in addition to skills training, more time for group discussion, and content adaptable to parents from diverse backgrounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Merlino et al (2020) have shown that external support structures consisting of family and friends play an integral role in imparting health literacy to young people, particularly indigenous males. Health literacy courses have been effective in leading towards better health outcomes in the Australian context (Muscat et al, 2020). Therefore, the use of productive measures can lead towards improvement in child health outcomes.…”
Section: Health Literacymentioning
confidence: 99%
“…Therefore, research is needed in culturally, linguistically, and socio‐economically diverse populations. Findings from studies, such as the ongoing SUCCESS trial, 28 which are trialing digital interventions in ethnically‐diverse populations, suggest that more targeted recruitment strategies to identify people with CKD with low health literacy are needed.…”
Section: The Potential Of Digital Interventions To Improve Health Beh...mentioning
confidence: 99%